2014
DOI: 10.1371/journal.pone.0097293
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Platelet-Rich Plasma (PRP) and Hyaluronate Acid on the Healing of Cartilage Defects

Abstract: Platelet-rich plasma (PRP) has offered great promise for the treatment of cartilage degradation, and has been proved to have positive effects on the restoration of cartilage lesions. But no comparative work has been done between PRP and hyaluronate acid (HA) concerning their restoring effect on cartilage defect, especially by means of animal experiments and histologic assessments. The purpose of the study was to compare the therapeutic effects of P-PRP and HA on osteoarthritis in rabbit knees. Thirty rabbits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…The clinical relevance of the synovial fluid COMP levels lies in the fact that higher concentration of synovial and serum COMP has been positively co-related with symptomatic OA 1,2,10,16 . Thus, indirectly, when we evaluate our equivocal histopathological results along with significant COMP level changes in PRP treated knees, our results could corroborate those of Kazemi et al 12 and Liu et al 19 indicating a beneficial effect of PRP on articular cartilage.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The clinical relevance of the synovial fluid COMP levels lies in the fact that higher concentration of synovial and serum COMP has been positively co-related with symptomatic OA 1,2,10,16 . Thus, indirectly, when we evaluate our equivocal histopathological results along with significant COMP level changes in PRP treated knees, our results could corroborate those of Kazemi et al 12 and Liu et al 19 indicating a beneficial effect of PRP on articular cartilage.…”
Section: Discussionsupporting
confidence: 86%
“…Saito et al 28 co-cultured adult rabbit chondrocytes in 3% PRP and showed increased in vitro chondrocyte GAG production. Liu et al 19 demonstrated improved cartilage and subchondral bone restoration via micro CT in a rabbit model after creating 5 mm defects in femoral condyles and treatment with 3 weekly PRP injections as compared to controls and hyaluronic acid treated groups. Kazemi et al 12 showed healing of surgically made chondral defects in PRP treated knees in a canine model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few reports are available concerning the effect of PRP on acute cartilage injury. 13,14 Because the superficial layer of articular cartilage is typically subjected to high levels of cyclic shear and tensile stress during joint motion and because overloading observed in continual strenuous exercises results in a physiological imbalance, 15 an ideal in vitro model should involve a continuous mechanical load exerting injurious effects. A number of studies have investigated the effect of cyclic tensile strain (CTS) on chondrocytes.…”
mentioning
confidence: 99%
“…At week 12, the IL-1β level in the P-PRP group was lower than in the HA group (p < 0.01) and in the control group (p < 0.01). The restoration of the defected cartilage as well as the subchondral bone was better in the P-PRP group than in the HA group or the control group (P < 0.05) [ 34 ].…”
Section: Prp In Cartilage Regenerationmentioning
confidence: 84%